Cortical Reshaping and Functional Recovery Induced by Silk Fibroin Hydrogels-Encapsulated Stem Cells Implanted in Stroke Animals - Fernández-García, Laura; Pérez-Rigueiro, José; Martinez-Murillo, Ricardo; Panetsos, Fivos; Ramos, Milagros; Guinea, Gustavo V.; González-Nieto, Daniel (Frontiers in Cellular Neuroscience, 2018)
The restitution of damaged circuitry and functional remodeling of peri-injured areas constitute two main mechanisms for sustaining recovery of the brain after stroke. In this study, a silk fibroin-based biomaterial efficiently supports the survival of intracerebrally implanted mesenchymal stem cells (mSCs) and increases functional outcomes over time in a model of cortical stroke that affects the forepaw sensory and motor representations. We show that the functional mechanisms underlying recovery are related to a substantial preservation of cortical tissue in the first days after mSCs-polymer implantation, followed by delayed cortical plasticity that involved a progressive functional disconnection between the forepaw sensory (FLs1) and caudal motor (cFLm1) representations and an emergent sensory activity in peri-lesional areas belonging to cFLm1. Our results provide evidence that mSCs integrated into silk fibroin hydrogels attenuate the cerebral damage after brain infarction inducing a delayed cortical plasticity in the peri-lesional tissue, this later a functional change described during spontaneous or training rehabilitation-induced recovery. This study shows that brain remapping and sustained recovery were experimentally favored using a stem cell-biomaterial-based approach.